Explosive ordinance disposal: Motion sensor simulator in Nintendo Wii - Mentzelopoulos, Markos; Tanasa, Mihai; Protopsaltis, Aristidis; Economou, Daphne (SIGDOC'11 - Proceedings of the 29th ACM International Conference on Design of Communication, 2011)
Simulation based games attempt to replicate real life or fiction scenarios for the purposes of learning, training, investigating or predicting results. This paper presents a case study of a simulation based on terrestrial which are primarily used by Explosive Ordinance Disposal Units (E.O.D.) in the investigation and disposal of bomb threats in Nintendo Wii, to examine different methods and techniques of player immersion, adaptation and learning. The paper presents background research that has been conducted for the design and implementation of the E.O.D. simulator. The simulated environment demonstrates its usefulness over a number of real bomb scenarios where player has to actively inspect the environment to locate and dispose of any potential bomb threats in an efficient manner. © 2011 ACM.
Created from Fastlane, Scopus look-up
Keywords: aabb (axis aligned bounding box); avt (automatic video tracking); game engine; igs (image generators); object oriented; oobb (object aligned bounding box); peo stri (program executive office for simulation; training and instrumentation); sdk (software development kit); sivet (simulated infrared/visible engagements with targets); vr (virtual reality); xna pipeline